2016
DOI: 10.1016/j.tranon.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression and Survival among Patients with Advanced Non–Small Cell Lung Cancer Treated with Chemotherapy

Abstract: BACKGROUND: Recent clinical trial results have suggested that programmed cell death ligand 1 (PD-L1) expression measured by immunohistochemistry may predict response to anti–programmed cell death 1 (PD-1) therapy. Results on the association between PD-L1 expression and survival among patients with advanced non–small cell lung cancer (NSCLC) treated with chemotherapy are inconsistent. MATERIAL AND METHODS: We evaluated the relationship between PD-L1 expression and overall survival (OS) among 204 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 32 publications
(38 reference statements)
12
62
3
Order By: Relevance
“…High PD-L1 has also been reported to be a favourable prognostic factor in small cell lung carcinomas(43) as well as breast carcinoma (16), colorectal adenocarcinoma (14), gastric cancer(44) and melanoma (23). These results are at odds, however, with two recently presented abstracts on NSCLC (40,45) using the same Merck 22C3 PD-L1 antibody as in our study. One study found high PD-L1 expression was associated with poor overall survival in a Korean population of early and advanced stage NSCLC, particularly in ADCs (40).…”
Section: Page 14 Of 31contrasting
confidence: 53%
See 1 more Smart Citation
“…High PD-L1 has also been reported to be a favourable prognostic factor in small cell lung carcinomas(43) as well as breast carcinoma (16), colorectal adenocarcinoma (14), gastric cancer(44) and melanoma (23). These results are at odds, however, with two recently presented abstracts on NSCLC (40,45) using the same Merck 22C3 PD-L1 antibody as in our study. One study found high PD-L1 expression was associated with poor overall survival in a Korean population of early and advanced stage NSCLC, particularly in ADCs (40).…”
Section: Page 14 Of 31contrasting
confidence: 53%
“…One study found high PD-L1 expression was associated with poor overall survival in a Korean population of early and advanced stage NSCLC, particularly in ADCs (40). In the other study looking at a European population of patients with advanced stage NSCLC M a n u s c r i p t WA Cooper et al 16 treated with chemotherapy, there was no association between PD-L1 expression and overall survival (45). A number of earlier studies found high PD-L1 was associated with a poorer prognosis in NSCLC (8,10,11,40) as well as several other solid human tumors including carcinoma of the pancreas(13), oesophagus (46), liver(47), ovary (17), kidney (19), urothelium (20), and melanoma (21).…”
Section: Page 14 Of 31mentioning
confidence: 98%
“…Furthermore, IHC PD-L1 positivity in NSCLC has been identified as a potential predictor of response to anti– PD-1 and anti–PD-L1 monoclonal antibody therapy (96) and also as a prognostic biomarker (97). Other studies reported that PD-L1 overexpression cannot be currently considered a robust predictive biomarker for response to immunotherapy or a prognostic biomarker (98). These discrepancies may be due to assay variability and interpretive subjectivity differences for the evaluation of PD-L1 expression, including differences in detection methods, IHC antibody clones, and cut-off values for determining PD-L1 positivity, and heterogeneity in PD-L1 expression and site of PD-L1 expression (tumor cells and tumor inmune cells) (99, 100).…”
Section: Immunotherapy Markers In Lung Cancermentioning
confidence: 99%
“…However, when the relationship between PD-L1 expression and OS among chemo-treated patients was evaluated, no obvious association was observed in median or tertile PD-L1 expression levels. 56 Several investigations to ascertain whether polymorphisms of genes involved in immune checkpoints may affect anti-tumor immune activity, thereby influencing clinical outcomes of chemotherapy in NSCLC patients, have been conducted. Lee et al 44 investigated the effects of the genetic polymorphisms of immune checkpoints on patients after first-line chemotherapy.…”
Section: Predictive Markers Of Anti-pd-1/pd-l1 Therapymentioning
confidence: 99%